How Do Positions of Phosphito Units on a Calix[4]Arene Platform Affect the Enantioselectivity of a Catalytic Reaction? - Shaima Hkiri; David Sémeril (Organics, 2022)
Three chiral diphosphites, (S,S)-5,17-bis(1,1′-binaphthyl-2,2′-dioxyphosphanyloxy)-25,26,27,28-tetrapropyloxycalix[4]arene (1), (S,S)-5,11,17,23-tetra-tert-butyl-25,27-dipropoxy-26,28-bis(1,1′-binaphthyl-2,2′-dioxyphosphanyloxy)calix[4]arene (2) and (S,S)-5,11,17,23-tetra-tert-butyl-25,26-dipropoxy-27,28-bis(1,1′-binaphthyl-2,2′-dioxyphosphanyloxy)calix[4]arene (3), based on conical calix[4]arene were investigated in the rhodium-catalyzed asymmetric hydrogenation of α-dehydroamino esters. High conversions were observed after 24 h under 5 bar of hydrogen whatever the employed diphosphite, and the chiral induction increases in the order 1 < 3 < 2. This may be due to the presence of the calix[4]arene moiety, which by its presence modifies the second coordination sphere of the catalytic center. The larger steric hindrance around the rhodium atom leads to the higher enantiomeric excess.